Efficient ozone catalysis by manganese iron oxides/activated carbon for sulfamerazine degradation. (October 2022) - Liu, Xinghao; Zhu, Wenxiu; Yang, Zhaoguang; Yang, Ying; Li, Haipu
Abstract: In this study, the manganese iron oxides/activated carbon (Mnx Fey Oz /AC) was prepared via the simple co-precipitation method, characterized and used for ozone catalytic degradation of sulfamerazine (SMZ). The best catalytic ozonation activity of Mnx Fey Oz /AC was obtained at a ratio of Fe/Mn = 1:11.2. The degradation ratio (~90.5 %) was improved by 25.7 % compared to that of ozonation system. The effects of various factors, including SMZ concentrations, ozone dosage, catalyst dosage, and initial pH on the catalytic performance were investigated. The presence of organic matter and ions in rivers, tap-water, and secondary effluent could decrease the catalytic performance. The Mnx Fey Oz /AC could promote more ozone dissolution in solution, while the surface hydroxyl as active sites could promote the production of hydroxyl radicals. The hydroxyl radical could destroy the SMZ structure by the cleavage of SN and CS bonds, and hydroxylation of aniline. The results of toxicity assessment indicated that catalytic ozonation could effectively control the acute and chronic toxicity of the SMZ water samples. In addition, the results of characterization of Mnx Fey Oz /AC before and after the ozonation experiments were discussed, and a possible degradation mechanism was proposed. Importantly, the electrical energy per order value was about 1.37 kW·h/(m 3  h −1 ), which was lower than those of other technologies. This work presents an efficient and promising catalytic ozonation technique for the elimination of SMZ from solution, and provides interesting information for the elucidation of the mechanism of action. Graphical abstract: Unlabelled Image Highlights: Magnetic Mnx Fey Oz /AC was synthesized via simple co-precipitation method. The best catalytic activity was obtained at the ratio of Fe/Mn = 1:11.2. Surface hydroxyl groups played an important role in ozone decomposition. The possible transformation products and pathways were proposed.